COMMUNICATION PATTERNS OF VIRTUAL IDOL “PLAVE” AND FANS THROUGH THE YOUTUBE APPLICATION ON @PLAVE_OFFICIAL - Dewi, Meliyana Wati; Oktoviani, Lia; Komalasari, Komalasari; Khumayah, Siti; Nurfalah, Farida (Ridwan Institute, 2024)
YouTube has become a platform that makes it easy for its users to exchange messages. On this platform, a new phenomenon has emerged regarding virtual streamers who use avatars to interact with viewers on their YouTube channels. This study uses a qualitative method with a netnographic approach that emphasizes direct observation with visual materials in collecting data and in-depth interviews with 2 informants. The researcher aims to formulate an interaction process that is woven from existing communication patterns, which will produce certain outcomes. The researcher made the virtual idol PLAVE the subject of the study and found that the interactions carried out by the virtual idol with his fans formed a communication pattern that encouraged the formation of a virtual community. In this community, there was finally an exchange of messages that influenced each other. Therefore, a strong sense of loyalty and emotional synchronization was formed between the virtual idol and his fans.